STUDENTS’ PERCEPTION ON ENGLISH-MEDIUM INSTRUCTION IN ICP PROGRAM - Abu, Muthmainnah; Mahfuddin, Musyrifah; Uleng, Budiarti Putri (Universitas Andi Djemma, 2025)
This study aims at investigating 1) the extent to which the students are satisfied with the ICP program they attend, 2) the perception of the students towards the courses and materials offered in the ICP program they attend and 3) the perception of the students towards the impact of the ICP program they attend might have on their language learning and future. This study is a survey research employing a survey method. The subjects of this research include 66 students taken from 6 study. The instrument used is a questionnaire consisting of 3 sub-scales, namely Satisfaction, Courses and Materials, and Language Learning and Future Each sub- scale contains 10 items with the total number of items is 30. The data collected was analyzed quantitatively with the assistance of SPSS version 25.0. The findings of this research reveal that 1) the majority of the students participating in this research had a high level of satisfaction in relation to the ICP program they attended, 2) most students perceived the courses and materials they encountered in the ICP program to be good and 3) the majority of the students perceived the ICP program to be influential to their language learning and future.